Review of Research on the Rare-Earth Doped Piezoelectric Materials - Chen, Yan; Zhang, Donglai; Peng, Zhong; Yuan, Maodan; Ji, Xuanrong (Frontiers in Materials, 2021)
The piezoelectric materials, such as ceramics, crystals, and films, have wide applications in the mechanical industry, medical imaging, electronic information, and ultrasonic devices, etc. Generally, adding oxide dopants, or introducing new solid solutions to form the morphotropic phase boundary of the piezoelectric materials were common strategies to enhance the electric properties. In recent decades, rare-earth elements doped piezoelectric materials have attracted much attention due to their multifunctional performances combining piezoelectric and photoluminescence properties, which has potential applications in ultrasonics, electronics, automatic control, machinery and optoelectronic fields. An overview of the recent investigations and perspectives on rare-earth doped piezoelectric ceramics, single crystals, and films were presented.